Analysis of laminar and turbulent natural, mixed and forced convection in cavities by heatlines - Hernández-López, I.; Xamán, J.; Álvarez, G.; Chávez, Y.; Arce, J. (Archives of Mechanics, 2016)
Laminar and turbulent convective heat transfer in a ventilated and non-ventilated cavity was analyzed by heatlines. Heatlines show that in non-ventilated cavities it is possible to estimate the energy path using the streamlines for turbulent flow regime. In ventilated cavities, heatlines allow to observe that thermal energy travels along the top, by the bottom or by both paths due to the inertial force, the buoyant force or a combination of both, respectively. In the laminar regime, these situations are well established for the Rayleigh number (Ra). Nevertheless, in the turbulent regime, it was found that the combined effect of the inertial and buoyant forces on the energy path is disrupted when Ra > 109. Furthermore, heatlines in conjunction with temperature and velocity profiles allow to see that natural convection is preferred when cooling is required, while the forced convection is a better choice if heating is needed.